Evaluación in vitro de cepas de Bacillus sp, aislados de la Antártida, como promotoras de crecimiento en Zea mays L - Zambrano Solorzano, Angela Beatriz (2021)
This research was developed in the Molecular Biology laboratory of the Veterinary Medicine career at Escuela Superior Politécnica Agropecuaria de Manabí "Manuel Félix López", with the aim of evaluating in vitro the plant growth promoting capacity of 83 isolated Bacillus sp strains at the Ecuadorian Experimental Station Pedro Vicente Maldonado in Antarctica. The isolates were evaluated: Gram stain, catalase and hemolysis test, phosphate solubilization, siderophore production, growth without a N source, and survival at different values of temperature, ph and nacl. According to the desirable characteristics as plant growth promoters, three Bacillus sp strains were selected that were inoculated in two types of substrates (a. Clay and b. Compost + Clay) sterilized and deposited in glass beakers (200 cc), in each A Trueno variety maize seed was placed in a glass; 15 days after germination, the seedling height (AT), root length (LR) and stem diameter (DT) were measured. In the interaction of the factors under study and the simple effect of the Bacillus sp strains, no statistical differences were found in the variables evaluated; the general averages were 15.28 cm (AP), 12.84 cm (LR) and 2.26 cm (SD). The Compost + Clay substrate statistically influenced in favor of LR and DT with averages of 14.44 and 2.38 cm, respectively. It is concluded that the results achieved are promising and it would be necessary to continue validating the selected microorganisms in productive environments.